Case Report: Hepatic infantile hemangioma malignantly transformed into hemangiosarcoma - Gu, Xiafei; Tao, Qing; Lu, Zijian; Liu, Jianping; Zhang, Zhang; Lu, Changli (Frontiers in Oncology, 2025)
In this study, we retrospectively analyzed the clinicopathological features of a case of hepatic infantile hemangioma (HIH) that malignantly transformed into hemangiosarcoma. HIH, a congenital disease, is the most common benign tumor of the liver in children, and its malignant transformation into hepatic angiosarcoma (HAS) is rare. HIH expresses markers of vascular origin and specifically expresses glucose transporter protein isoform 1. When the malignant transformation of HAS occurs, the vascular lumens anastomose with each other and form a sieve mesh, with pseudo-papillae and solid areas, heterogeneous proliferation of tumor cells, spindle/or epithelioid morphology, heterogeneous distribution of chromatin, enlarged nuclei, and pathologic karyotypes, with strong diffuse positivity of P53 and P16, increased Ki-67 proliferative activity, suggest malignant transformation of HAS. Imaging is the preferred examination method for HIH; however, the presence or absence of characteristic changes in HAS is unclear. There is no uniform treatment guideline for this type of tumor, and a reasonable individualized treatment plan should be formulated according to the specific conditions of the children. There is a lack of case reports of the malignant transformation of HIH into HAS. It is unclear whether HIH treatment should be still extended, and the prognosis is also unclear; therefore, more case reports are needed to accumulate experience.